Cost-effectiveness analysis of anastrozole versus tamoxifen in adjuvant therapy for early-stage breast cancer: a health-economic analysis based on the 100-month analysis of the ATAC trial and the German health system - Lux, Michael Patrick; Wöckel, Achim; Benedict, Agnes; Buchholz, Stefan; Kreif, Noémi; Harbeck, Nadia; Kreienberg, Rolf; Kaufmann, Manfred; Beckmann, Matthias Wilhelm; Jonat, Walter; Hadji, Peyman; Distler, Wolfgang; et al. (Oncology research and treatment, 2010)
In the ‘Arimidex’, Tamoxifen Alone or in Combination (ATAC) trial, the aromatase inhibitor (AI) anastrozole had a significantly better efficacy and safety profile than tamoxifen as initial adjuvant therapy for hormone receptor-positive (HR+) early breast cancer (EBC) in postmenopausal patients. To compare the combined long-term clinical and economic benefits, we carried out a cost-effectiveness analysis (CEA) of anastrozole versus tamoxifen based on the data of the 100month analysis of the ATAC trial from the perspective of the German public health insurance. Patients and Methods: A Markov model with a 25-year time horizon was developed using the 100-month analysis of the ATAC trial as well as data obtained from published literature and expert opinion. Results: Adjuvant treatment of EBC with anastrozole achieved an additional 0.32 quality-adjusted life-years (QALYs) gained per patient compared with tamoxifen, at an additional cost of D 6819 per patient. Thus, the incremental cost effectiveness of anastrozole versus tamoxifen at 25 years was D 21,069 ($30,717) per QALY gained. Conclusions: This is the first CEA of an AI that is based on extended follow-up data, taking into account the carryover effect of anastrozole, which maintains the efficacy benefits beyond therapy completion after 5 years. Adjuvant treatment with anastrozole for postmenopausal women with HR+ EBC is a cost-effective alternative to tamoxifen.
Gesehen am 20.04.2023